Impact of the School Literacy Movement on Reading Skills of Grade I Students: Dampak Gerakan Literasi Sekolah terhadap Keterampilan Membaca Siswa Kelas I - Lestari, Triwidya; Astuti , Ruli (Indonesian Journal of Education Methods Development, 2023)
The weak levels of reading and writing skills among the Indonesian population have become a pressing education issue in the country. In response, the government introduced the School Literacy Movement program in 2015, aiming to foster a reading culture among students. This study employs a quantitative approach to analyze the effect of the School Literacy Movement on the reading skills of grade I students at SD Muhammadiyah 2 Tulangan. Data collection techniques included tests and questionnaires, with a sample of 24 students. The results indicate that the School Literacy Movement has a significant positive impact on students' reading skills, as reflected in an Adjusted R Square value of 73.8%. Over 50% of students displayed excellent reading abilities, indicating the effectiveness of the literacy initiative. This research highlights the importance of the School Literacy Movement in enhancing reading proficiency among young learners and calls for continued support and implementation of similar programs to improve education outcomes in Indonesia. Highlight: The study addresses the issue of weak reading and writing skills among the Indonesian population, and the government's response through the implementation of the school literacy movement program. Using a quantitative method, the research analyzes the impact of the school literacy movement on the reading skills of grade I students at SD Muhammadiyah 2 Tulangan, with a sample size of 24 students. The findings reveal a significant positive effect of the school literacy movement on students' reading skills, as indicated by an Adjusted R Square value of 73.8%. More than 50% of students displayed excellent reading abilities, underscoring the success of the literacy initiative in fostering diligent reading habits among young learners. Keyword: Weak Literacy, School Literacy Movement, Reading Skills, Grade I Students, Quantitative Method